Empowering Families with DAGUSIBU (Dapatkan, Gunakan, Simpan, Buang) : Promoting Safe and Responsible Medicine Management in The Teluk Sanggar Community, Banjar Regency, South Kalimantan - Pribadi, Anjar; Norsyipa, Norsyipa; Putri, Arvina Rafika; Salman, Yuliana; Zaini, Muhammad; Husin, Husin (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aimed to enhance public understanding of the DAGUSIBU concept (Dapatkan, Gunakan, Simpan, Buang) as part of an educational effort to promote safe and responsible medication management within the family environment. The methods employed included Focus Group Discussions (FGD) and counseling, with evaluations carried out through pretest and posttest assessments to measure changes in participants' knowledge. The program involved 32 residents of Teluk Sanggar Village, Martapura District, Banjar Regency, with 53.13% male and 46.87% female participants. The evaluation results indicated a significant increase in participants' knowledge after the intervention. The percentage of participants in the "Poor" category decreased from 87% to 0%, while the "Good" and "Excellent" categories increased to 28%. To further validate the significance of these changes, a Wilcoxon signed-rank test was conducted. The results of the test confirmed a statistically significant difference in knowledge scores before and after the intervention (p < 0.05). This supports the conclusion that the DAGUSIBU education was effective in improving participants' understanding of proper medication management. These findings demonstrate that DAGUSIBU education effectively raises public awareness of safe medication practices. Future programs are recommended to develop more detailed educational materials, engage healthcare professionals, and implement ongoing monitoring at the household level.